A visual guide to human development and diseases (Visual exploration of science., 2019)
Provides a visual guide to human development and diseases, discussing topics such as fetal development, microlife, common diseases, and advanced medicinal technology. Includes extensive graphics and images, a glossary, sources for further learning, and an index.